Effect of Different Anionic Ligands on Toxicity of Silver Nanoparticles - Chen, Shao-Feng; Zhang, Hongyin (Asian Journal of Chemistry, 2012)
Silver nanoparticle nanosuspension was prepared by Tollen's method using sodium citrate as stabilizing agent. Particle size and zeta potential of silver nanoparticles in different electrolyte solutions containing anionic ligands and humic acid solution were characterized by zetasizer. Dissolution of silver nanoparticels was evaluated using ICP-MS. Toxicity of silver nanoparticles on Escherichia coli were measured using a plate count method. The obtained results showed that toxicity of silver nanoparticles in electrolyte solution containing Cl– ligands was significantly reduced. Among all the conditions, toxicity of silver nanoparticles in humic acid solution was the lowest.